(untitled) (Papeles, 2017)
This article is derived from a diagnostic exercise of the performance of five teachers of Spanish language in fifth level of elementary school in five schools of different socio-economic status. To this aim three matrices were developed to analyze class planners, notebooks and written tasks in an academical term, in order to determine to what extent the disciplinary and pedagogical competences performed by teachers influenced the development of the writing process of their students.